2020
DOI: 10.2460/javma.256.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of surgeon's perception of the effectiveness of spinal cord decompression with findings on postoperative magnetic resonance imaging for dogs surgically treated for intervertebral disk extrusion

Abstract: OBJECTIVE To determine the accuracy of the surgeon's perception versus postoperative MRI findings in assessing the effectiveness of spinal cord decompression achieved in dogs surgically treated for intervertebral disk extrusion (IVDE) and whether postoperative MRI findings were more likely to be associated with various outcomes. ANIMALS 68 dogs surgically treated for cervical or thoracolumbar IVDE. PROCEDURES Data on clinical, neurologic, pre- and postoperative MRI, and intraoperative findings as well as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…A common categorization is based on the percentage of reduction in spinal cord diameter, graded as mild (<25%), moderate (25 to 50%), or severe (>50%) (102,103). Morphometric estimates of crosssectional area of either spinal cord or extruded material offer even more precise information (104)(105)(106). The degree of spinal cord compression seen on transverse MR images in cases of IVDE was associated with the severity of pre-operative neurological signs in the cervical spine (107), but not in the thoracolumbar region (94,108,109).…”
Section: Mri Findings In Intervertebral Disc Extrusionmentioning
confidence: 99%
See 4 more Smart Citations
“…A common categorization is based on the percentage of reduction in spinal cord diameter, graded as mild (<25%), moderate (25 to 50%), or severe (>50%) (102,103). Morphometric estimates of crosssectional area of either spinal cord or extruded material offer even more precise information (104)(105)(106). The degree of spinal cord compression seen on transverse MR images in cases of IVDE was associated with the severity of pre-operative neurological signs in the cervical spine (107), but not in the thoracolumbar region (94,108,109).…”
Section: Mri Findings In Intervertebral Disc Extrusionmentioning
confidence: 99%
“…Interestingly, a recent low-field MRI study of IVDE found spinal cord hyperintensity on T2W images in 18% of dogs in the preoperative period. MRI was repeated after decompressive surgery (immediately after surgery in most dogs) and the number of dogs with hyperintensity almost doubled (34%) (105). The relationship between spinal cord hyperintensity and prognosis of IVDD can be found in the article "Prognostic factors in acute spinal cord injury" in this issue.…”
Section: Mri Findings In Intervertebral Disc Extrusionmentioning
confidence: 99%
See 3 more Smart Citations